2011
DOI: 10.1097/qai.0b013e318237ca80
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Family Planning and HIV Care Services on Contraceptive Use and Pregnancy Outcomes

Abstract: Objective To determine the impact of routine care (RC) and integrated family planning (IFP) and HIV care service on family planning (FP) uptake and pregnancy outcomes. Design Retrospective cohort study conducted between October 10, 2005, and February 28, 2009. Setting United States Agency for International Development—Academic Model Providing Access To Healthcare (USAID-AMPATH) in western Kenya. Subjects Records of adult HIV-infected women. Intervention Integration of FP into one of the care teams. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 23 publications
1
64
0
3
Order By: Relevance
“…35 Other methods of contraception such as sterilisation, intrauterine devices (IUDs) and hormonal contraceptives are more effective, but do not protect against HIV transmission or acquisition of other sexually transmitted infections (STIs). Thus, using only condoms for dual protection against HIV/STIs and unintended pregnancy is not as reliable or effective as dual method use, 38 which combines consistent condom use with a highly effective contraceptive method. 36 However, studies indicate that fewer than 20% of PLHIV in sub-Saharan Africa report dual method use.…”
Section: Introductionmentioning
confidence: 99%
“…35 Other methods of contraception such as sterilisation, intrauterine devices (IUDs) and hormonal contraceptives are more effective, but do not protect against HIV transmission or acquisition of other sexually transmitted infections (STIs). Thus, using only condoms for dual protection against HIV/STIs and unintended pregnancy is not as reliable or effective as dual method use, 38 which combines consistent condom use with a highly effective contraceptive method. 36 However, studies indicate that fewer than 20% of PLHIV in sub-Saharan Africa report dual method use.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing TB among pregnant women remains a challenge in Kenya. Kosgei and colleagues (47) found TB symptom screening questionnaires to be less useful than chest X-rays to identify TB suspects in both symptomatic and asymptomatic women. Physiological changes associated with pregnancy, as well as women living with HIV, may mask the symptoms of TB.…”
Section: Lack Of Accessible Health Care For Diagnosis and Treatment: mentioning
confidence: 99%
“…[19][20][21] Some cohort studies have documented that integrated services can decrease pregnancy rates 22 and increase uptake of hormonal contraceptive methods. 23,24 Most recently, the first cluster-randomized trial (CRT) of integrating FP into routine HIV care services, conducted in western Kenya, demonstrated an increase in more effective contraception use, from 17% at baseline to 37% one year after integration in the intervention arm. 16 The trial also found the intervention to be cost-effective.…”
mentioning
confidence: 99%